Parole Officer Decision-Making Before Parole Revocation: Why Context Is Key When Delivering Correctional Services - Ostermann, Michael (Criminal justice policy review, 2022)
Back-end sentencing is the discretionary, administrative process through which individuals on parole are returned to prison for violating the requirements of their supervised release. Parole officers play a crucial role in this process as they are the witnesses to the rule-breaking behaviors of people on parole supervision and ultimately must initiate the back-end sentencing process. This study explores predictors of parole officer decision-making when determining whether to consider a person for revocation or to gear programmatic community-based resources toward them in an attempt to decrease the likelihood of their eventual revocation. Our results indicate that if people released to parole are front-loaded programmatic resources as a part of their release conditions from prison, the odds that parole officers subsequently gear community-based programs toward them decreases by approximately 60%. Other factors such as demographics, actuarial risk levels, and criminal history were not significantly predictive of officer decision-making in this context.